The Effect of Study Habits on the Learning Outcomes of Natural and Social Sciences (IPAS) at Elementary School Students - Febianti, Dwi; Rezania, Vanda (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Study habits are a way or technique to establish students when receiving learning, reading books, and doing assignments to complete teaching and learning activities. With these good Study habits, students can improve learning outcomes from the scores obtained previously. This study aims to determine the effect of student study habits on student learning outcomes in class IV Natural and Social Sciences (IPAS) subjects at SDN Kedensari II. This research is a quantitative study using the post facto approach. The population in this study was grade IV students, and the research sample was 50 students. Data collection in this study is the first to use a questionnaire and documentation of mid-semester test scores as learning outcomes in Natural and Social Sciences (IPAS) subjects. Data analysis used descriptive analysis, prerequisite test analysis, and hypothesis testing with the T-test, and the results showed that students' study habits were included in a reasonably good category with a percentage of 38%. The value of learning outcomes from the midterm test scores was included in the good enough type, with the highest rate of 34%. This research proves that Study habits significantly affect student learning outcomes in class IV Natural and Social Sciences (IPAS) subjects at SDN Kedensari II.